KAjIAN METODOLOGI DAN SIGNIFIKANSINyA DALAM PENGEMBANGAN DISIPLIN ILMU EKONOMI ISLAM - Hafas Furqani (IAIN Langsa, 2016)
Abstrak.Methodology, the study of science philosophy is generally included in the study of epistemology discussing the nature, sources, concepts and theories of science. Therefore, it follows the development of epistemology study and philosophy of science, although both of them are different in terms of their focus and scope of assessment. Epistemology discusses the theory of science, nature and its limitations, but the methodology is more arguing about the specific studies to examine how a theory born and its evaluation. As a new discipline, methodology study is very essential to build the scientific foundations of Islamic Economics producing its own theories. Solid methodology eases to raise the scientific structures of Islamic economics from the source of its discipline, utilizing its own scientific foundation. This paper examines the link between Islamic epistemology and the methodology of Islamic economics, the nature and the definition of the methodology itself and its significance in constructing the technical of Islamic economics.Keywords: epistemology, methodology, discipline, significance, Islamic economics